IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI UPTD SD INPRES OESAPA - Eni Rambu Habati; Marlen Angela Daik; Donal Jidon Josanto Biaf (STKIP Pesisir Selatan, 2026)
This study aims to describe the implementation of facility and infrastructure management in improving the quality of learning at the UPTD SD Inpres Oesapa, Kelapa Lima District, Kupang City. This study uses a descriptive qualitative approach with a case study design. Data collection techniques were carried out through observation, in-depth interviews, and documentation involving the principal, teachers, and administrative staff as key informants. The results of the study indicate that the management of facilities and infrastructure, including planning, procurement, distribution, utilization, maintenance, inventory, and disposal, has not been implemented optimally. The main obstacles faced include budget limitations, the lack of Standard Operating Procedures (SOPs), especially at the procurement and utilization stages, and an inventory system that is still carried out manually and not digitally. This condition has an impact on the less than optimal utilization of facilities and infrastructure in supporting the learning process. Therefore, innovation is needed through the implementation of digital-based management and the preparation of standardized SOPs to improve the effectiveness, efficiency, transparency, and accountability of the management of educational facilities and infrastructure.